Music, whiteness and experimentalism: critical perspectives (PerCursos, 2021)
This paper approaches the perpetuation of epistemic racism in the musical field, from the colonial period to the contemporary contexts. By looking at universalizing assumptions linked to the focus on the materiality of sound, apart from socio-political contextual implications, tensions and incompatibili-ties between musical experimentalism and political activism are delineated. Finally, the article points out recent initiatives of decolonial potential in the experimental context.
Keywords: whiteness; whiteness' narcissistic pact; experimental music; decolonial studies